Serial multiple mediating role of coping style and anxiety in the relationship between life events and academic satisfaction in Chinese medical undergraduates - Yang, Jiarun; Song, Xuemei; Zhang, Jili; Zheng, Yunge; Chen, Guangyu; Bu, Tianyi; Zhou, Jiawei; Tong, Yuying; Yang, Yanjie; Qiao, Zhengxue (Frontiers in Public Health, 2024)
ObjectivesAcademic satisfaction plays an important role in promoting the future careers of medical undergraduates. Therefore, it is of great significance to improve academic satisfaction by exploring its influencing factors. The purpose of this study was to investigate the serial multiple mediating role of life events, coping styles, anxiety, and academic satisfaction among Chinese medical students.MethodsIn this cross-sectional study, clinical medicine students from a medical university in Heilongjiang Province were surveyed using stratified random cluster sampling procedures. The questionnaires included the Adolescent Life Events Scale, the Simple Coping Style Questionnaire, the Self-rating Anxiety Scale, and the Academic Satisfaction Scale. Pearson’s correlation analysis and bootstrap analysis were used for statistical analysis.ResultsLife events were negatively related to positive coping styles and academic satisfaction and were positively related to anxiety symptoms. Positive coping styles were negatively associated with anxiety symptoms and positively associated with academic satisfaction. Anxiety symptoms were negatively associated with academic satisfaction. The serial multiple mediating role of positive coping style and anxiety in the relationship between life events and academic satisfaction was significant.ConclusionThe results showed that life events were sequentially associated with decreased positive coping styles and then increased anxiety, which resulted in reduced academic satisfaction among medical students.